How is it spelled: cebiche, ceviche, seviche or sebiche? - Jesús Martín Crisólogo Galván (2025)
This article examines the different spellings of the emblematic Peruvian dish known as cebiche, ceviche, seviche, or sebiche, from the perspective of linguistic correctness. It highlights the orthographic guidelines of the Royal Spanish Academy (RAE), which accepts several variants but prioritizes “cebiche.” The study also presents the views of scholars such as Federico More, Martha Hildebrandt, Javier Pulgar Vidal, and Juan José Vega, who propose diverse etymological origins ranging from the Spanish word “cebo” to Arabic, Quechua, and Mochica roots. Furthermore, the influence of cultural syncretism after the Spanish conquest is discussed, particularly the incorporation of Andean and Hispanic ingredients that shaped the modern preparation. The article also considers alternative hypotheses, such as a possible English origin from “Sea beach.” Ultimately, it underscores that beyond orthographic or historical debates, ceviche has become a cultural symbol of Peru, officially declared a National Cultural Heritage, with multiple accepted spellings reflecting both linguistic norms and social usage.